Alveolar Bone and Epithelial Attachment Status following Two Different Closed-eruption Surgical Techniques for Impacted Maxillary Central Incisors: A Recent Study - Sfeir, Elia; Gholmieh, Mona; Skaf, Zouhair; Mourad, Ayman (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
Aim: For the treatment of upper impacted central incisors (ICIs), two main surgical approaches are typically described: open and closed. The closed-eruption surgical method (CEST) is currently the most popular because it provides the best esthetic and periodontal benefits. The purpose of this study was to see how traction discontinuation affected maxillary central incisor sulcal depth and alveolar bone ridge levels when compared to contralateral incisors when CEST was used. Materials and Methods: CEST was used to treat 28 unilaterally impacted maxillary central incisors. At the time of crown emergence, thirteen teeth were subjected to a month of traction interruption, whereas 15 teeth were subjected to continuous traction. The ICIs and contralateral central incisors (CCIs) were subjected to periapical digital X-rays, anterosuperior cone beam computed tomography (CBCT) scanning, and periodontal probing one year following treatment. The CCI measurements were utilized as a reference, and the Student's t-test was employed to see if there was a statistically significant difference between continuous and interrupted tractions. Results: Only the following measurements showed a statistically significant difference between the two techniques: Mesial probing (p-value 0.039352), labial bone level (p-value 2.58E-08), and palatal bone level (p-value 2.56E-06). Limitations: To draw more robust conclusions, a larger sample size and longer term follow-up are required. Conclusion: On ICIs, a temporary discontinuation during tooth traction appears to improve treatment outcome. Technical modifications and the use of a temporary interruption during tooth traction can result in better treatment outcomes. Clinical significance: The CEST leads to the best periodontal status for ICIs. The discontinuation of traction at the emergence of the tooth allows the supracrestal fibers to insert into the cement in a proper way.